Thickened Liquids Improve Infant Swallow Function as Measured by Penetration‐Aspiration Scale Score on Videofluoroscopic Swallow Study - Golden, Clare; Kim, Michael; Larson, Kara; Duncan, Daniel R. (Pediatric pulmonology, 2025)
Thickened liquids are commonly used to treat oropharyngeal dysphagia in infants but the extent to which each viscosity improves swallow function is not well understood. Our objective was to determine improvements in swallow function with provision of thickened liquids as measured by penetration-aspiration scale (PAS) score changes on videofluoroscopic swallow study (VFSS). We performed a retrospective cohort study of infants with aspiration or laryngeal penetration on VFSS. Records were reviewed for highest PAS reported, whether thickened liquids were tested, PAS for each viscosity, and PAS for viscosities recommended after VFSS. Safe swallow was defined as PAS ≤ 2. Proportions were compared with Fisher exact tests and means with t-tests. The cohort included 521 infants of whom 60% (310) had laryngeal penetration and 40% (211) aspiration with 93% (197/211) silent aspiration. Thickening was evaluated during VFSS in 71% (371) of patients and was more likely to be tested in infants that were older, had higher starting PAS score, deep and consistent laryngeal penetration, and aspiration (p < 0.001). The proportion of infants with safe swallowing was found to increase with increasing liquid viscosity with 73% (112/153) showing safe swallowing with mildly thick consistency. Of the 300 infants for whom thickening was recommended, 96% (287) were able to achieve PAS 1 or 2. Thickened liquids have a viscosity-dependent therapeutic effect in the treatment of infants with oropharyngeal dysphagia. Our results suggest it may be possible to facilitate safe swallowing in the majority of infants by using liquids at mildly thick consistency.